Effects of Rotenone and Resveratrol on Apoptosis and Oxidative Stress in Ovariectomized Rats - Mahboobeh Aghagolzadeh; AhmadAli Moazedi; Hossein Najafzadehvarzi; Hadi Parsian (مجله دانشگاه علوم پزشکی گیلان)
Background Exposure to neurotoxins increases the risk of neurodegenerative diseases. Oxidative stress and apoptosis play a central role in the initiation and progression of these disorders. Low estrogen aggravates oxidative stress and apoptosis caused by neurodegenerative diseases in menopausal women. Therefore, the use of resveratrol with antioxidant and protective properties and signaling pathways common with estrogen, can be a useful therapeutic approach in preventing the progression of oxidative stress and apoptosis. Objective The present study aims to investigate the protective effect of resveratrol on the antioxidant factors and rotenone-induced apoptosis in the hippocampus of ovariectomized rats. Methods Thirty female rats were divided into five groups of 6, including rotenone (5 m/kg), ovariectomized, ovariectomized+rotenone, ovariectomized+resveratrol (40 m/kg), and ovariectomized+rotenone+resveratrol. Rotenone was administered intraperitoneally, and resveratrol was administered orally for 21 days. In the end, Malondialdehyde (MDA), superoxide dismutase (SOD), and expression of BAX and BCL2 genes were measured in the hippocampus. Results Enzyme activity and BCL2 expression in the rotenone and ovariectomized groups significantly decreased, while BAX expression and MDA level significantly increased. Resveratrol significantly increased enzyme activity (57.9±1.94 U/mg protein) and BCL2 expression (0.78±0.05) in the ovariectomized + rotenone + resveratrol group (P<0.001). Also, resveratrol significantly reduced BAX expression (4.5±0.11) and MDA level (1.91±22.35 µM/g) in this group (P≤0.001). Conclusion Resveratrol corrected the simultaneous effects of low estrogen and rotenone consumption on changes in apoptosis gene expression and oxidative stress factors and returned to a normal level.